ACTIVITIES OF IRIS MURDOCH (Conference Zone, 2022)
The article presents a brief biography of the talented English writer Iris Murdoch and some information about his development as a writer. Iris Murdoch, both a scientist and a writer, has been particularly active in the modernist and postmodern world, with a cultural and spiritual crisis in society and a tumultuous influx of innovation. The work shows the unique creative path of the author, the features of the English character in his novels.